Preventing Underage Users from Accessing Social Media: A Blockchain-Based Age Verification Approach - Jadhav, Aditya; Paymode, Sameer (Journal of Advanced Research in Signal Processing and Applications, 2024)
This research paper explores how Blockchain-Based Age Verification can keep young users safe on social media while protecting their privacy. It offers a secure way to confirm age without revealing personal information, addressing the growing concern of underage users accessing online platforms. This research paper examines the efficacy of Blockchain-Based Age Verification in mitigating the risks associated with underage users accessing social media platforms. By leveraging blockchain technology, this approach ensures a secure verification process while safeguarding user privacy. The paper discusses the challenges posed by existing age verification methods and explores the unique features of blockchain that make it a robust solution. It reviews literature on current age verification practices and identifies privacy concerns, false information, user experience, and legal issues as key challenges. Principles of blockchain technology, including decentralization, immutability, cryptography, consensus mechanisms, privacy-preserving features, and transparency, are elucidated to demonstrate its suitability for age verification. The paper also examines previous initiatives and strategies for encouraging user adoption of blockchain-based age verification. In conclusion, it underscores the potential of blockchain technology to revolutionize age verification processes on social media platforms, emphasizing the importance of user-friendly design and voluntary adoption strategies while navigating legal and ethical considerations.